Analysis of the game of actors for the management of the urban extension. case of the urban pole of the city of Bouira - Amir, Amar; Alkama, Djamal (Technium Social Sciences Journal, 2023)
The city is a very complex system produced by the various interventions carried out by different actors. The diversity of these actors influences the different decisions taken concerning the future, the development and the management of urban spaces in cities. In this perspective, it is essential to question the transformations experienced by these cities from the actors, while emphasizing their role and their impacts. Bouira is a medium-sized city that has undergone significant development in recent years, particularly in terms of spatial growth, which has been to the detriment of land with high agricultural potential. All the interventions in the city are carried out by different actors working in various fields, whose interests are not necessarily convergent. Indeed, "without a detailed analysis of the interplay of actors, the scenarios lack relevance and coherence" (Michel Godet, 2007). To this end, this article aims to analyze the game of actors contributing to the construction of a future image of the city of Bouira. Through the use of the Mactor method, we will define the nature of the relations between the different actors concerning the project of the urban pole of Bouira, while trying to define their roles, their direct and indirect influences between them and to identify their convergences and divergences.